The Routledge Handbook of Gender Politics in Sport and Physical Activity (Routledge, 2022)
This progressive and broad-ranging handbook offers a comprehensive overview of the complex intersections between politics, gender, sport and physical activity, shining new light on the significance of gender, sport and physical activity in wider society.